1994
DOI: 10.1108/eb039626
|View full text |Cite
|
Sign up to set email alerts
|

Royalties From Loyalties

Abstract: If quality begets customer satisfaction and customer satisfaction begets customer retention, why doesn't customer retention beget customer loyalty—and greater profits? Because loyalty's a fickle thing—and needs proper management to thrive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…One point of view is that loyalty is simply another term for customer retention; a customer who continues to buy is a loyal customer. However, Fay (1994) reports the case of one retail organisation which found that the customers it retained the longest were actually the least pro®table because of their strategic bargainseeking behaviour.…”
Section: Understanding Customer Loyaltymentioning
confidence: 95%
See 2 more Smart Citations
“…One point of view is that loyalty is simply another term for customer retention; a customer who continues to buy is a loyal customer. However, Fay (1994) reports the case of one retail organisation which found that the customers it retained the longest were actually the least pro®table because of their strategic bargainseeking behaviour.…”
Section: Understanding Customer Loyaltymentioning
confidence: 95%
“…Romano (1995) suggests that 65±70 per cent of encounters that meet or exceed the expected threshold of customer satisfaction merely involve hygiene factors, having no impact on customer loyalty. In a business-tobusiness survey, Fay (1994) found that while over 70 per cent of companies ranked price as the ®rst or second least satisfactory issue, interviews with switchers found that no more than 10 per cent had changed suppliers because of price. Satisfaction, therefore, seems a necessary, although insuf®cient, cause of loyalty.…”
Section: Satisfaction and Dissatisfactionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hoteliers need to keep employees longer, not only due to the cost of hiring and training new employees, but also tenured employees tend to provide a more positive performance, which is linked to customer satisfaction (Bedeian et al, 1992). Employee job satisfaction is directly associated with customer loyalty; customer loyalty is unequivocally related to profitability (Fay, 1994;Iaffaldano and Muchinsky, 1985); therefore, maintaining quality employees would be the ideal method to sustain a solid reputation and build a repeat customer base (Keane, 1996).…”
Section: Justification For Job Satisfaction Studymentioning
confidence: 98%
“…However, the fundamental goal for an organization is still customer retention or customer loyalty (Evans & Lindsay, 1996;Fay 1994;Gerson, 1993). Customer loyalty/ retention is the willingness of customers to repurchase from a particular organization.…”
Section: Dependent Variable (Perceived Service Quality (Psq))mentioning
confidence: 98%